Prior band-resisted squat jumps improves running and neuromuscular performance in middle-distance runners - Low, J. L.; Ahmadi, H.; Kelly, L. P.; Willardson, J.; Boullosa, D.; Behm, D. G. (Journal of Sports Science & Medicine, 2019)
Post-activation potentiation (PAP) conditioning has been reported to increase performance. Most research has examined PAP effects on strength/power activities, whereas the effects on endurance sports are understudied. The aim of this study was to characterize PAP conditioning stimulus effects on a subsequent 5x1 km running trial. A randomized, within subjects, repeated measures study utilized 12 male, endurance-trained athletes, who performed a full warm-up, conditioning exercise intervention (4x5 repetition maximum band-resisted squat jumps) or a control condition prior to a 5x1 km time trial run. Tests were conducted immediately prior to the intervention, after each kilometer, immediately following the 5x1 km run, and at seven and ten minutes post 5 km run. Measures included the interpolated twitch technique (ITT), evoked contractile properties, maximum voluntary isometric contractions (MVIC) plantar flexor force, drop jump, rating of perceived exertion, and heart rate. The PAP stimulus reduced the time to complete the run (3.6%; p = 0.07, d = 0.51), and decreased the time to complete kilometer one (8%; d = 1.08, p = 0.014). Jump height (p = 0.02; 9.2%) and reactive strength index (p = 0.035; 16%) increased with PAP. F100 (force produced in the first 100ms of the MVIC) and MVIC force with PAP increased at kilometers 3 (p = 0.04, d=0.84), 4 (p = 0.034, d = 0.29), and 7min post-run (p = 0.03, d = 0.60). Voluntary activation (ITT) increased at 7min post-run (p = 0.04, d = 0.59) with PAP, yet decreased at 7min post-run in the control condition (p = 0.03, d = 0.36). A prior band-resisted squat protocol decreased running time and improved neuromuscular properties in endurance athletes running 5x1 km.